ANALISIS DAKWAH BIL LISAN HABIB JA'FAR DALAM MENANAMKAN NILAI-NILAI MODERASI DAN TOLERANSI PADA ACARA POADCAST “CLOSE THE DOOR” - Nurislamiah, Mia; Waqi’ah, Ghina Nurul; Wandani, Regita Cahyani Puspa (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Dakwah bil lisan (preaching through speech) is a crucial method in conveying Islamic teachings, especially in today’s digital era. The "Close The Door" podcast, hosted by Deddy Corbuzier and featuring Habib Ja'far Al-Hadar, has become one of the most effective platforms for instilling values of moderation and tolerance in younger generations. This research aims to analyze how Habib Ja'far delivers inclusive messages of dakwah through appropriate language, narrative, and rhetoric. The methodology used in this study is a descriptive qualitative approach with discourse analysis. Data were collected from podcast episode transcripts and supported by triangulation with secondary sources such as audience comments on social media. The findings reveal that Habib Ja'far successfully captures the audience's attention with his relaxed and humorous preaching style while conveying messages of moderation relevant to the current social context. His wasathiyyah (moderation) approach to dakwah fosters awareness of the importance of tolerance and acceptance of diversity in society. Thus, this study provides new insights into the effectiveness of dakwah bil lisan through modern media and highlights Habib Ja'far's contribution to strengthening religious moderation among Indonesian youth. These findings are expected to serve as a reference for other preachers in utilizing digital platforms to deliver religious values effectively and engagingly.